A seminal study of Iban alphabet / Bromeley Philip - Philip, Bromeley (2007)
The Iban of Sarawak do not possess any form of writing system that can be used universally within its large community. There was however some interesting individual effort at inventing some forms of writing system. One known writing system is that invented by Dunging anak Gunggu, acknowledged in the Encyclopaedia of Iban Studies (2001). This Iban Alphabet is not an ancient system ofwriting as the inventor lived well into the mid-80s. The alphabet manifests the dynamism of a modern alphabet suitable for practical inscription. It comprises syllabic writing and alphabetic writing symbols.The former consists of syllabaries, representing syllables in the Iban language. The latter comprises true alphabet of consonants and individual vowels or vowel clusters. As a seminal work, the researcher categorised the alphabet into alphabetical writing symbols and phonetic/syllabic writing symbols for practical inscriptional purposes. The seminal research also involved “re-alphabetising” of several Romanised Iban language manuscripts and texts.